2021
DOI: 10.3390/w13050673
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Flow and Sediment Transport in the Lower Min River in Southeastern China under the Impacts of Climate Variability and Human Activities

Abstract: The Min River is the largest river in Fujian Province in southeastern China. The construction of a series of dams along the upper reaches of the Min River, especially the Shuikou Dam, which started filling in 1993, modified the flow processes at the lower Min River, leading to the significant increase in low-flows and slightly decrease in flood-flows. At the same time, reservoirs have more effects on the sediment transport process than flow process by trapping most sediment in the reservoirs, and greatly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…A major challenge, since ancient times, has been the problem of sediment accumulation in the reservoir bowl causing loss of capacity or complete siltation [61][62][63][64][65][66][67][68]. The suspension of sediment movement is associated not only with the loss of functionality of the facility, but also with the disturbance of the channel morphology below the dam cross-section [65].…”
Section: C23-sediment Accumulation [61-68]mentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge, since ancient times, has been the problem of sediment accumulation in the reservoir bowl causing loss of capacity or complete siltation [61][62][63][64][65][66][67][68]. The suspension of sediment movement is associated not only with the loss of functionality of the facility, but also with the disturbance of the channel morphology below the dam cross-section [65].…”
Section: C23-sediment Accumulation [61-68]mentioning
confidence: 99%
“…A major challenge, since ancient times, has been the problem of sediment accumulation in the reservoir bowl causing loss of capacity or complete siltation [61][62][63][64][65][66][67][68]. The suspension of sediment movement is associated not only with the loss of functionality of the facility, but also with the disturbance of the channel morphology below the dam cross-section [65]. Various methods of measuring sediment accumulation rates and sediment transport rates are described, based on a Geographic Information System (GIS), mathematical models, field surveys, historical data and photographic documentation [61][62][63][64].…”
Section: C23-sediment Accumulation [61-68]mentioning
confidence: 99%
“…The Min River basin (MRB), a densely populated area, has been grappling with water quality issues and recurrent flooding for several decades (Wang et al, 2021), largely attributed to rapid developmental activities reflecting anthropogenic influences. This situation accentuates the urgent need to reevaluate the interplay between economic development and ecological sustainability in the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers evaluated the impact of climate change and human activities on watershed hydrological variables [7][8][9][10][11][12][13], which indicated that the influence of a changing environment on the water cycle has been of concerned to more researchers. Among these articles, the hydrological variability under climate change and human influence in the Wuding River Basin was investigated [7]; the result shows that climate change and human influence drive both evapotranspiration and runoff changes.…”
mentioning
confidence: 99%
“…Among these articles, the hydrological variability under climate change and human influence in the Wuding River Basin was investigated [7]; the result shows that climate change and human influence drive both evapotranspiration and runoff changes. Wang et al [8] evaluated changes of flow and sediment transport in the Lower Min River under the impacts of the above two drivers. The research demonstrated that the reduction of precipitation is the leading cause of runoff reduction, followed by human activities.…”
mentioning
confidence: 99%